the modern system of customs measures for protection of rights for the objects of intellectual property - L. F. Tufetulova (Russian Journal of Economics and Law)
This article is devoted to the content of international system of measures, set by the Treaty if the World Trade Organization for the trade aspects of the intellectual property rights (IPR). The role and significance of the Russian customs service in this system are analyzed.